Tourism / Principles and Practice - Cooper, Chris; Fletcher John; Gilbert David (Longman, 1998)
A comprehensive grounding in the subject of tourism to all students. Preface, Abbreviations, An Introduction to Tourism, Tourism Demand, Concepts and Definitions and Indicators of Tourism Demand, Consumer Behavior and Tourism Demand, Models and Patterns of Tourism Demand, Measuring Demand for Tourism, The Tourism Destination, The Destination, The Economic Impact of Tourism, The Environmental Impact of Tourism, The Socio-cultural Impact of Tourism, Carrying Capacity, Tourism and Development Planning, The Tourism Industry, Government Organizations, Intermediaries, Transportation, Attractions, Accommodation, Marketing for Tourism, Marketing for Tourism - The Historical Roots, Marketing Management for Tourism, Marketing Planning, The Marketing Mix, The Future of Tourism, Information Technology, The Future of Tourism, Major Case Studies, Index.